Experimental investigation of heavy oil recovery by continuous/WAG injection of CO2 saturated with silica nanoparticles. (1st January 2015) - Jafari, Saeed; Khezrnejad, Ayub; Shahrokhi, Omid; Ghazanfari, Mohammad Hossein; Vossoughi, Manouchehr
In this work, application of CO2 saturated with silica nanoparticles in continuous/water alternating gas (WAG) injection for heavy oil recovery was investigated which has been rarely attended in the available literature. Core displacement tests were conducted to monitor heavy oil recovery in both continuous and WAG injection schemes. It has been observed that for continuous nano-saturated CO2 injection, the oil recovery is higher than pure CO2 injection. This observation might be explained by alteration of rock wettability to a more water-wet condition. In WAG injection scheme, water breakthrough happened later in nano-saturated CO2 than pure CO2 injection. This delayed water breakthrough can be caused by nano-stabilised oil in water emulsions. These oil emulsions hindered the oil recovery before breakthrough. However, recovery factor of WAG injection of nano-saturated CO2 exceeded that of pure CO2 as those stabilised oil emulsion were produced along with water after breakthrough. The results of this work reveal that saturation of CO2 with silica nanoparticles can improve the microscopic efficiency of continuous CO2 injection, while in CO2 WAG injection this hampers oil recovery before water breakthrough.